Studi Literatur Riview: Manajemen Karir Meningkatkan Kinerja dan Kepuasan Kerja Karyawan - Dian Septiani Wibowo; Ismail Yahya Saputra; Rendy Supriyanto; Mochammad Isa Anshori (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Career management is a crucial process for both individuals and organizations. For individuals, it facilitates the achievement of career goals and enhances job satisfaction. For organizations, it aids in attracting, developing, and retaining qualified employees. This study delves into the factors influencing career management, encompassing individual factors (abilities, skills, interests, values, and personality), organizational factors (organizational culture, structure, career opportunities, and career policies), and environmental factors (economic, socio-political, and technological conditions). The findings demonstrate that effective career management can enhance employee career effectiveness, job satisfaction, and organizational performance. The study also provides recommendations for improving career management, including regular career assessments, career development program development, information and training, a supportive organizational culture, and encouraging employees to proactively manage their careers. Further research is warranted to develop more effective and contextual career management models and investigate the impact of career management on other factors such as organizational commitment, employee turnover, and gender equality in the workplace.